2020
DOI: 10.1002/cbic.201900698
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Destabilization of Bacterial Membranes by Quaternary Ammonium Compounds: A Combined Experimental and Computational Study

Abstract: In special dedication to Dr.Faina Ryvkin for her many years of servicet os tudents at Emmanuel College, Boston.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…The interaction of the VCM-loaded StBAclm-Qt1 quatsomes with the MRSA could be due to the antibacterial activity of quaternary bicephalic surfactant, which resulted in the effective delivery of the VCM, leading to bacteria membrane disruption. Quaternary ammonium compounds have long been assumed to disrupt bacterial membranes through electrostatic attraction, followed by intercalation and subsequent disruption [ 95 ]. The investigation into how the quatsomes were functionalized revealed that Gram-positive bacteria (MRSA) appear to be affected by the antimicrobial properties of the quatsomes.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of the VCM-loaded StBAclm-Qt1 quatsomes with the MRSA could be due to the antibacterial activity of quaternary bicephalic surfactant, which resulted in the effective delivery of the VCM, leading to bacteria membrane disruption. Quaternary ammonium compounds have long been assumed to disrupt bacterial membranes through electrostatic attraction, followed by intercalation and subsequent disruption [ 95 ]. The investigation into how the quatsomes were functionalized revealed that Gram-positive bacteria (MRSA) appear to be affected by the antimicrobial properties of the quatsomes.…”
Section: Resultsmentioning
confidence: 99%
“…They are bactericidal across a range of microorganisms, including fungi, bacteria, parasites and lipophilic viruses [ 10 ]. Due to their aliphatic nature, QACs act as cationic surfactants; therefore, they destabilize the cell membranes and enzymes of target microorganisms, resulting in cell lysis [ 11 , 12 , 13 ]. Examples include benzalkonium chloride and cetylpyridinum chloride, both of which can target Gram-negative and Gram-positive bacteria such as Escherichia coli and Staphylococcus aureus , respectively [ 14 ].…”
Section: Quaternary Ammonium Compounds (Qacs)mentioning
confidence: 99%
“…Further, all of the tested N‐alkylpyridinium compounds displayed remarkable selectivity for Gram‐positive bacteria surpassing that of CPC and BAC. This result is normally indicative of a mechanism of action involving disruption of the plasma membrane, considering the low hemolytic activity seen in Table 1 it is likely that these compounds are permeabilizing the membrane and not lysing akin to recent discoveries in our lab [8] . Compound 8 shows an added level of selectivity, showing an 8 fold preference to inhibit the growth of S. mutans relative to S. aureus .…”
Section: Figurementioning
confidence: 76%
“…Many QACs can attribute their antimicrobial activity to their amphipathic nature, allowing for permeabilization and eventual lysis of plasma membranes [8] . This often results in selective inhibition of Gram‐positive bacteria, as these species lack the additional outer membrane seen in Gram‐negative bacteria.…”
Section: Figurementioning
confidence: 99%